Spiritual Synchronicity: Icon Veneration in Evangelical and Orthodox Religious Practices in the 21st Century - Cannon, Mae Elise (Religions, 2021)
Much scholarship in the dialogue between evangelical and Orthodox believers focuses on doctrinal compatibility. This article contributes to that literature by giving an example of a spiritual practice (icon veneration) that creates additional space for ecumenical dialogue and unity. Some US-evangelicals in the 21st century have incorporated the use of icons into their personal faith practices. Icon veneration is ripe with ecumenical potential for evangelical-Orthodox relations because of its prominence in Orthodox communions while at the same time appealing to a growing number of evangelicals. This article considers three sites of evangelical icon use in turn: the Evangelical Baptist Church of Georgia (EBCG), Icons of Black Saints, and an evangelical ministry called “Heart of the Artist”. Each site adopts a slightly unique understanding of icons that may appeal to evangelical believers. Although Orthodox and evangelical believers may understand theologies of icon veneration differently, the emergence of icon veneration among evangelicals remains a spiritual synchronicity, and ought to be recognized as such. Evangelicals continue to receive the gift of icon veneration from their Orthodox siblings in ways in line with the EBCG, Black Orthodox icons, and Heart of the Artist, so icon veneration has potential to further resource ecumenical dialogue.